To find the inverse of a function, follow these simple steps:
Start with the function: Write the function as ( y = f(x) ).
Switch ( x ) and ( y ): Change the equation to ( x = f(y) ).
Solve for ( y ): Get ( y ) all by itself on one side of the equation.
Rewrite ( y ): Change ( y ) to ( f^{-1}(x) ). This shows the new function you're finding.
Check your work: Make sure that ( f(f^{-1}(x)) = x ) and ( f^{-1}(f(x)) = x ).
Now you have the steps to find the inverse function easily!
To find the inverse of a function, follow these simple steps:
Start with the function: Write the function as ( y = f(x) ).
Switch ( x ) and ( y ): Change the equation to ( x = f(y) ).
Solve for ( y ): Get ( y ) all by itself on one side of the equation.
Rewrite ( y ): Change ( y ) to ( f^{-1}(x) ). This shows the new function you're finding.
Check your work: Make sure that ( f(f^{-1}(x)) = x ) and ( f^{-1}(f(x)) = x ).
Now you have the steps to find the inverse function easily!